2003
DOI: 10.1063/1.1624246
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterization of HOONO and its binding energy via infrared action spectroscopy

Abstract: The trans-perp (tp) conformer of peroxynitrous acid (HOONO), a secondary product of the OH + NO 2 reaction and a less stable isomer of nitric acid, has been identified by infrared action spectroscopy in the OH overtone region after being generated in a pulsed supersonic expansion. Rotational structure associated with the OH overtone band of tp-HOONO has been observed at 6971.4(1) cm-1 (origin) and assigned by simulating its band structure using a transition dipole moment and rotational constants derived from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 24 publications
5
52
0
Order By: Relevance
“…1, 6,16 and isomerizes quickly to the more stable cis-cis conformer ͑millisecond time scale at room temperature and ϳ10 Torr͒. 6 Fry et al therefore attribute all of the bands reported by Nizkorodov and Wennberg to the lowest energy conformer, cis-cis HOONO.…”
Section: -4mentioning
confidence: 99%
“…1, 6,16 and isomerizes quickly to the more stable cis-cis conformer ͑millisecond time scale at room temperature and ϳ10 Torr͒. 6 Fry et al therefore attribute all of the bands reported by Nizkorodov and Wennberg to the lowest energy conformer, cis-cis HOONO.…”
Section: -4mentioning
confidence: 99%
“…Hippler, Nasterlack, and Striebel report the only experimental value, D 0 (cis-cis HOONO)ϭ83 kJ/mol, from a third-law analysis of the equilibrium constants over 430-490 K. 3 A refinement of the evaluation of this data is underway, and reanalysis of the high temperature data now gives D 0 (cis-cis HOONO)ϭ80.5 kJ/mol. 16 Pollack et al 17 have set an experimental upper limit on the trans-perp HOONO binding energy of 70.3 kJ/mol from the product internal energy distribution of the vibrational predissociation of jetcooled trans-perp HOONO. From this limit and the ab initio energy difference between cis-cis and trans-perp HOONO, they find an upper limit for the cis-cis HOONO dissociation energy, D 0 (cis-cis HOONO)р84.6 kJ/mol.…”
Section: Fig 1 Energy Level Diagram For the Ohϩnomentioning
confidence: 99%
“…Subsequently, Pollack et al definitively identified the first OH stretching overtone of supersonically cooled trans-perp HOONO from the rotational band contours detected with photodissociation action spectroscopy. 17 Though the band origin at 6971.4 cm Ϫ1 lies close to the strongest band seen by Nizkorodov and Wennberg, the band is expected to be substantially narrower even at room temperature.…”
mentioning
confidence: 99%
“…This work was followed in rapid succession by detection of the cis-cis 1 fundamental by Bean et al using cavity ringdown spectroscopy 16 and a high-resolution study of the trans-perp 2 1 band in a supersonically cooled molecular beam by Pollack et al 17 18 The vibrational frequencies and intensities calculated in this study enabled Lee and co-workers 11,13 to distinguish between the trans-perp and cis-cis conformers in their matrix IR spectra. McGrath and Rowland subsequently used G2, G2͑MP2͒, QCISD(T)/6-311G(d,p), and MP2 calculations with basis sets up to 6-311ϩG͑3df,2p͒ to improve characterization of the relative energetics of the three stable conformers.…”
mentioning
confidence: 99%
“…A combined submillimeter and infrared experiment could also be used to quantify the band strengths of the infrared transitions. 14,16,17 This research was performed at the Jet Propulsion Laboratory ͑JPL͒, California Institute of Technology, under contract with the National Aeronautics and Space Administra- …”
mentioning
confidence: 99%